Designed synthesis of SiC nanowire-derived carbon with dual-scale nanostructures for supercapacitor applications. Issue 26 (20th June 2018) - Zou, Xingli; Ji, Li; Hsu, Hsien-Yi; Zheng, Kai; Pang, Zhongya; Lu, Xionggang
Abstract : A simple approach has been designed for the synthesis of mesoporous silicon carbide-derived carbon nanowires (SiC-CDC NWs) for supercapacitor applications. Abstract : The preparation of one-dimensional carbon materials with complex dual-scale nanostructures for supercapacitor applications still remains a challenge. Herein we report a simple strategy for electrosynthesis of silicon carbide nanowire (SiC NW)-derived carbon with dual-scale nanostructures for high performance supercapacitors. This method is highlighted by using solid oxide membrane technology to directly convert powdered silicon dioxide/carbon precursors into SiC NWs, and then the synthesized SiC NWs are further transformed into mesoporous silicon carbide-derived carbon nanowires (SiC-CDC NWs) via a subsequent in situ molten salt electrochemical etching process. Benefitting from their dual-scale nanostructures, these SiC-CDC NWs exhibit highly reversible specific capacitance of 260 F g −1 at 1 A g −1 and good cyclability (97.9% after 5000 cycles) in 6 M KOH aqueous solution without the need for doping the SiC-CDC NWs. It is suggested that this process is a promising general approach for synthesizing CDC materials with dual-scale nanostructures for energy storage applications.